Band Edge Engineering of Oxide Photoanodes for Photoelectrochemical Water Splitting: Integration of Subsurface Dipoles with Atomic‐Scale Control. Issue 7 (22nd January 2016) - Hikita, Yasuyuki; Nishio, Kazunori; Seitz, Linsey C.; Chakthranont, Pongkarn; Tachikawa, Takashi; Jaramillo, Thomas F.; Hwang, Harold Y.
Abstract : One of the crucial parameters dictating the efficiency of photoelectrochemical water‐splitting is the semiconductor band edge alignment with respect to hydrogen and oxygen redox potentials. Despite the importance of metal oxides in their use as photoelectrodes, studies to control the band edge alignment in aqueous solution have been limited predominantly to compound semiconductors with modulation ranges limited to a few hundred mV. The ability to modulate the flat band potential of oxide photoanodes by as much as 1.3 V, using the insertion of subsurface electrostatic dipoles near a Nb‐doped SrTiO3 /aqueous electrolyte interface is reported. The tunable range achieved far exceeds previous reports in any semiconductor/aqueous electrolyte system and suggests a general design strategy for highly efficient oxide photoelectrodes. Abstract : Flat band potential at an oxide semiconductor/aqueous electrolyte interface is systematically shifted over 1.3 V by atomically engineering an electrostatic dipole layer near this interface. Coherent stacking of polar oxide surfaces stabilizes a large internal electric field over atomic distances. This technique enables the decoupling of the bulk and interface constraints in designing photoelectrodes using complex oxides.